Coverage of anti-influenza vaccination in the elderly, Minas Gerais, Brazil (Research, Society and Development, 2021)
Influenza is an acute viral infection, immunopreventable, transmitted through the respiratory secretions of a person infected by the influenza virus. After the introduction of the Influenza vaccine in the vaccination calendar of the elderly, it was possible to notice a reduction in cases of pneumonia and deaths due to complications resulting from influenza. In view of the importance of vaccination for the elderly, this study aimed to analyze the anti-influenza vaccine coverage in the elderly in Minas Gerais (MG). Method: This is a cross-sectional study, using data from the 2017 vaccination campaign. Data were collected from the bases of the Information System of the National Immunization Program - SIPNI, Primary Care Information System - SISAB and Instituto Brasileiro de Geography and Statistics - IBGE. Results: The anti-influenza vaccine coverage in the West Region was 95.6%. Among the 53 municipalities in this region, the majority (84.9%) reached the goal of 90% influenza vaccination coverage, as recommended. Population size and family health team coverage in the municipalities were not associated with vaccination coverage, with a p-value of 0.697 and 0.949, respectively. Conclusion: The study demonstrated high vaccination coverage in the elderly in the Western Region of MG and this coverage was not influenced by the presence of SAI and the population size of the municipalities.